PENGARUH MEDIA FLASH CARD DALAM PEMBELAJARAN PENDIDIKAN PANCASILA “HAK DAN KEWAJIBAN DIRUMAH DAN DISEKOLAH” TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV DI SEKOLAH DASAR - Dony, Petrus Mau Tellu; Wabang, Yermia S.; Fanpada, Nehemia; Imanuel Yosafat Hadi Manapa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of Pancasila education for fourth-grade students, because teachers do not use varied learning media. The purpose of this study is to determine the Effect of Flash Card Media in Learning Pancasila Education "Rights and Obligations at Home and at School" on the Learning Outcomes of Fourth-grade Students of UPTD SD Negeri Pailelang. This study uses a pre-experimental method of quantitative research with a one-group approach (pretest posttest) with a sample size of 21 students. The sampling technique is saturated sampling. In this study, the data collection technique was through tests with a one-group pretest posttest research design. Furthermore, a prerequisite test for normality was carried out at 0.083. After that, a test was carried out with a hypothesis test using the Paired Sample t-test after which the data was analyzed using SPSS 22 and obtained the results of t-test 11,206 and t-table 1,725, meaning t-table > t-table, so H0 was rejected and H1 was accepted. From these results, it can be concluded that using flash cards in Pancasila Education learning on "Rights and Obligations at Home and at School" at the Pailelang Elementary School Technical Implementation Unit (UPTD) can improve student learning outcomes.